2009
DOI: 10.1021/es803306n
|View full text |Cite
|
Sign up to set email alerts
|

Mercury Removal from Flue Gases by Novel Regenerable Magnetic Nanocomposite Sorbents

Abstract: Magnetic zeolite composites with supported silver nanoparicles are a new class of multifunctional materials with potential applications as recyclable catalysts, disinfectants, and sorbents. This study evaluated the suitability of the magnetic composites as sorbents for the removal of elemental mercury vapor from flue gases of coal-fired power plants. The sorbents were found to completely capture mercury at temperatures up to 200 degrees C, and the mercury capacity of the sorbents was found to be affected by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
105
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 144 publications
(107 citation statements)
references
References 30 publications
2
105
0
Order By: Relevance
“…4.9 wt % of mercury was adsorbed). These findings indicate that it is possible that different gas than nitrogen is needed to regenerate silver impregnated zeolite, what seems to be supported by the other work -Dong et al [37] reported regeneration in argon, while Weekman et al -in methane [38]. Future work will aim to fully investigate zeolites regeneration potential along with the impact of gasification and combustion flue gas components on the sorbents mercury adsorption and its thermal stability.…”
Section: Thermal Gravimetric Analysissupporting
confidence: 56%
“…4.9 wt % of mercury was adsorbed). These findings indicate that it is possible that different gas than nitrogen is needed to regenerate silver impregnated zeolite, what seems to be supported by the other work -Dong et al [37] reported regeneration in argon, while Weekman et al -in methane [38]. Future work will aim to fully investigate zeolites regeneration potential along with the impact of gasification and combustion flue gas components on the sorbents mercury adsorption and its thermal stability.…”
Section: Thermal Gravimetric Analysissupporting
confidence: 56%
“…However, higher operating costs and negative effects on fly ash quality limited its wide application. Thus, great efforts have been devoted to develop cost-effective and ultrafine sorbents with highly effective sorption capacities and rapid reaction kinetics [8,9]. Considering the attractive economical factors, wet flue gas desulfurization (WFGD), a selective technology for sulfur dioxide (SO 2 ) removal adopted by US coal-fired power plants was recommended for removal of Hg [7].…”
Section: Introductionmentioning
confidence: 99%
“…51 In this case the catalyst is prepared using a magnetic zeolite, i.e. a natural chabazite containing also erionite and clinoptilolite, treated with magnetite to make it Schematics of the mercury removal and drying section in natural gas plant, with mercury recovery from the regeneration gas.…”
Section: Silver Zeolites As Regenerable Mercury Removal Adsorbentsmentioning
confidence: 99%